Making International Legal Persons in Investment Treaty Arbitration: State-owned Enterprises along the Person/Thing Distinction - Mikko Rajavuori (German Law Journal, 2022)
Investment treaty arbitration (ITA) has emerged as a space where the international legal personality of states and foreign investors is continuously created, maintained, and redefined. Focusing on treatment of state-owned enterprises (SOEs), this Article juxtaposes investment law’s doctrinal foundations with Roberto Esposito’s political philosophy to explore the dynamics, porosity, and ramifications of international legal personality in ITA. Skeptical of gradual conceptualizations of legal personality, this Article frames investment law in terms of Esposito’s person/thing distinction and argues for SOEs to form a liminal category that exposes malleability of legal doctrines when ITA tribunals make or break international legal persons. Ultimately, the ITA cases seem to open a distinct dispositif  of a SOE that both delineates the exact normative demarcation of the state as international legal person and creates pockets of indistinguishability and politics at its borders—often to the detriment of the Global South. This insight provides a new perspective on creation of international legal persons in ITA and international law more generally but, at the same time, also adds a new dimension to Esposito’s overarching framework resting on the asymmetric relationship between persons and things.